Analysis of Antioxidant and Fiber Content in Edamame Pudding (Glycine max) as a Snack to Prevent Hypercholesterolemia - Ismawati, Nur Ayu; Anggraeni, Anna (Institute of Accounting Research and Novation (IARN), 2024)
This research explores the antioxidant and fiber content of edamame pudding (Glycine max) and its potential health benefits, particularly in preventing hypercholesterolemia. Edamame, a rich source of antioxidants such as isoflavones and phenolic compounds, is known for its ability to combat oxidative stress and reduce cardiovascular risk. Additionally, its high fiber content, particularly soluble fiber, plays a significant role in lowering LDL cholesterol levels. This study analyzes the antioxidant levels and fiber content in edamame pudding and evaluates its potential to serve as a health-promoting snack. The findings highlight the pudding’s role in cholesterol management, heart disease prevention, and weight control. Edamame pudding offers a practical and nutritious alternative to traditional snacks, with the potential to support cardiovascular health. Recommendations for further research include long-term clinical trials to assess the sustained effects of edamame pudding on heart health and studies comparing its nutrient bioavailability to other health-promoting snacks.